Heart Rate Monitoring, Blood Oxygen Levels and Location Determination for Covid 19 Patients Using Internet of Things Technology - Sipahutar, Erwinsyah; Oktrison; Budiansyah, Arie; Candra, Rudi Arif; Ilham, Dirja Nur (Yayasan Cita Cendekiawan Al Khwarizmi, 2023)
The COVID-19 virus is very dangerous. In addition to attacking the lungs, this virus can also attack the heart directly. The relationship between heart health and COVID-19 occurs because blood vessel clots in COVID-19 patients increase the risk of blood vessel disorders and make the heart work harder. Therefore, researchers designed a heart rate monitoring device. This tool serves to maintain heart health and oxygen levels in the patient's blood and can also monitor people under COVID surveillance. The formulation of the problem from this research is how to design an IoT system to monitor COVID-19 patients through heart rate and location and how it performs. The purpose of this study is to analyze the performance of the device and design a tool to measure heart rate and blood oxygen levels through the IoT system and GPS location so that doctors can access heart rate data from any location. This research method uses a Gy-MAX30100 sensor, Wemos, and a GPS module. Of the 2 data samples that have been tested, the highest heart rate value is 78 bpm, the lowest is 76 bpm, and the highest oxygen level is 95 mmHg and the lowest is 93 mmHg. So in conclusion, this tool can make it easier for doctors to get important information about the condition of patients or people under observation that can be accessed by doctors anywhere and anytime via the internet.